Semi-solid electrolyte, preparation method thereof and lithium metal battery
By grafting 2,4,3,5-di-O-methylene-D-gluconic acid on MOF material, MOF-glucose complex was prepared, which solved the problems of uneven structure of the composite electrolyte and insufficient conductivity. A high-performance semi-solid electrolyte is achieved, improving the circulation performance and stability of the battery.
Patent Information
- Application Number
- CN202411722053.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
AI Technical Summary
The ionic conductivity improvement of the existing composite electrolytes is limited and the structure is uneven, resulting in poor membrane stability and poor cell circulation.
The MOF-glucose complex was prepared and bonded to the activated MOF material by mixing 2,4,3,5-di-O-methylene-D-gluconic acid and solvent for grafting reaction. The agent and solvent are mixed to make a thin film, soaked and dried by the electrolyte to obtain a semi-solid electrolyte with high room temperature ionic conductivity and uniform structure.
The high room temperature ion conductivity and uniform structure of the semi-solid electrolyte are realized, which improves the stability of the separator and the cycling performance of the battery, and has a high lithium ion transfer coefficient and a wide electrochemical stability window.
Smart Images

Figure BDA0005158282200000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a semi-solid electrolyte and a preparation method thereof, and a lithium metal battery. Background Art
[0002] At present, the energy density of lithium-ion batteries based on graphite anodes has approached its theoretical limit, which makes it difficult to meet the needs of emerging industries such as electric vehicles, smart grids, and robots for high specific energy and high safety energy storage devices. Therefore, it is urgent to develop the next generation of high energy density secondary battery systems. Lithium metal anodes have an ultra-high theoretical specific capacity (3860mAh g -1 ) and extremely low redox potential (-3.04 V, relative to standard hydrogen electrode), it is the most promising negative electrode candidate material for high energy density batteries. However, the flammability of liquid electrolytes and the safety hazards caused by the uncontrollable growth of lithium dendrites during battery charging and discharging have seriously hindered the practical application of lithium metal negative electrodes.
[0003] Solid electrolytes have the characteristics of good thermal stability and no leakage, better chemical and electrochemical stability, and high mechanical strength, which can effectively inhibit the growth of dendrites. Therefore, when matched with high-voltage positive electrode materials, a battery with high energy density can be obtained by combining their respective advantages and disadvantages. Therefore, solid-state batteries have the characteristics of high safety and high energy density at the same time, and are the most ideal solution for developing a new generation of energy storage batteries.
[0004] Solid electrolytes can be divided into two categories: inorganic solid electrolytes and polymer solid electrolytes. Among them, inorganic solid electrolytes usually have high mechanical strength and can effectively inhibit the growth of lithium dendrites, but they have disadvantages such as high density, high interface impedance and easy side reactions with electrodes, which seriously limit their practical applications. Polymer solid electrolytes have the advantages of easy processing, good flexibility and low interface impedance, but they have problems such as low room temperature ionic conductivity and insufficient mechanical properties, which also limit their application in lithium metal batteries.
[0005] In recent years, a strategy of combining inorganic fillers with polymer matrices to prepare tough organic-inorganic composite solid electrolytes has been proposed, which can simultaneously achieve high mechanical modulus and high ionic conductivity of solid electrolytes. The introduction of fillers can not only improve the mechanical modulus of composite electrolytes, but also reduce the crystallinity of polymer matrices, thereby achieving rapid lithium ion conduction.
[0006] Unfortunately, due to the poor compatibility of inorganic fillers with polymer matrices, conventional composite electrolytes obtained by simple mechanical blending often exhibit poor uniformity, resulting in limited improvement in the ionic conductivity of the composite electrolyte and uneven structure, leading to poor membrane stability and poor battery cyclability.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The first object of the present invention is to provide a method for preparing a semi-solid electrolyte, which can obtain a MOF material semi-solid electrolyte of chemically grafted polyether molecules, which has high room temperature ionic conductivity and uniform structure, good stability as a diaphragm, and excellent cycle performance of the assembled battery. It solves the problem that the ionic conductivity of the composite electrolyte prepared by the prior art is limited and the structure is uneven, resulting in poor membrane stability and poor battery cyclability.
[0009] The second object of the present invention is to provide a semi-solid electrolyte, which has high room temperature ionic conductivity and a uniform structure, and the semi-solid electrolyte has good stability. The battery made using the semi-solid electrolyte has excellent cycle performance, a high lithium ion transfer coefficient and a wide electrochemical stability window.
[0010] The third object of the present invention is to provide a lithium metal battery having excellent cycle performance, high energy density, high lithium ion transfer coefficient, and wide electrochemical stability window.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] The present invention first provides a method for preparing a semi-solid electrolyte, comprising the following steps: (a) mixing an activated MOF material with 2,4,3,5-di-O-methylene-D-gluconic acid and a solvent and performing a grafting reaction, and then performing solid-liquid separation to obtain a MOF-glucose complex; and (b) mixing the MOF-glucose complex, a binder and a solvent to obtain a slurry, and making the slurry into a film, immersing the film in an electrolyte, and then drying to obtain the semi-solid electrolyte.
[0013] Furthermore, in step (a), the 2,4,3,5-di-O-methylene-D-gluconic acid is mainly obtained by aldol condensation reaction of paraformaldehyde, D-gluconic acid-1,5-lactone and acid.
[0014] Furthermore, the mass ratio of the paraformaldehyde to the D-glucono-1,5-lactone is 4:1-4.
[0015] Furthermore, the acid includes at least one of concentrated hydrochloric acid and concentrated sulfuric acid.
[0016] Furthermore, the temperature of the aldol condensation reaction is 100-120°C.
[0017] Furthermore, the aldol condensation reaction time is 0.5 to 4 hours.
[0018] Furthermore, stirring is continued during the aldol condensation reaction.
[0019] Furthermore, the paraformaldehyde, the D-glucono-1,5-lactone and the acid are first mixed and subjected to an aldol condensation reaction, followed by solid-liquid separation, washing and drying to obtain the 2,4,3,5-di-O-methylene-D-gluconic acid.
[0020] Furthermore, in step (a), the mass ratio of the activated MOF material to the 2,4,3,5-di-O-methylene-D-gluconic acid is 7-9:2-3.
[0021] Furthermore, in step (a), the temperature of the grafting reaction is 60 to 90°C.
[0022] Furthermore, in step (a), the grafting reaction time is 24 to 48 hours.
[0023] Furthermore, in step (a), stirring is continued during the grafting reaction.
[0024] Furthermore, in step (a), the solvent includes water and / or an organic solvent.
[0025] Furthermore, in step (a), the solid-liquid separation further includes the steps of washing and drying.
[0026] Furthermore, in step (a), the method for preparing the activated MOF material comprises: immersing the MOF material in an activating agent for activation.
[0027] Furthermore, the activating agent includes at least one of acetone, acetonitrile, ethanol and dichloromethane.
[0028] Furthermore, the MOF material includes at least one of MOF-808, UiO-66 and UiO-67.
[0029] Furthermore, the preparation method of the MOF-808 includes: weighing zirconium oxychloride and 1,3,5-tricarboxylic acid in a mass ratio of 10:1-3, mixing with DMF and formic acid, reacting at 140-160°C for 24-48h, then separating the solid and liquid, washing and drying, and obtaining the MOF-808.
[0030] Furthermore, in step (b), the mass ratio of the MOF-glucose complex to the binder is 6-9:1-4.
[0031] Furthermore, in step (b), the binder includes at least one of PTFE, PVDF and CMC.
[0032] Furthermore, in step (b), the solvent includes water and / or an organic solvent, wherein the organic solvent includes at least one of ethanol, methanol and dichloromethane.
[0033] Furthermore, in step (b), grinding is performed during the mixing process.
[0034] Furthermore, in step (b), the method of making the slurry into the film comprises: coating the slurry on the surface of a substrate, drying it, and then applying a pressure of 8 to 12 MPa for 20 to 40 minutes to obtain the film.
[0035] Furthermore, in step (b), the lithium salt in the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluorosulfonyl)imide, and the organic solvent in the electrolyte includes at least one of ethylene carbonate, dimethyl carbonate and propylene carbonate.
[0036] Furthermore, in step (b), the soaking time is 48 to 72 hours.
[0037] The present invention further provides a semi-solid electrolyte prepared by the method for preparing the semi-solid electrolyte.
[0038] Furthermore, the ionic conductivity of the semi-solid electrolyte at 25°C is ≥1×10 -4 S cm -1 .
[0039] Furthermore, the capacity retention rate of the battery containing the semi-solid electrolyte after 500 cycles at 1C is ≥95%.
[0040] Furthermore, the lithium ion transfer coefficient of the battery containing the semi-solid electrolyte is ≥0.6.
[0041] Furthermore, the electrochemical stability voltage of the battery containing the semi-solid electrolyte is ≥5.4V.
[0042] The present invention also provides a lithium metal battery, comprising a semi-solid electrolyte prepared by the method for preparing the semi-solid electrolyte.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) The preparation method of the semi-solid electrolyte provided by the present invention can obtain a MOF material semi-solid electrolyte of chemically grafted polyether molecules (2,4,3,5-di-O-methylene-D-gluconic acid), which has high room temperature ionic conductivity and uniform structure, good stability as a diaphragm, and the assembled battery has excellent cycle performance.
[0045] (2) The semi-solid electrolyte prepared by the preparation method of the semi-solid electrolyte provided by the present invention has a higher lithium ion transfer coefficient and a wider electrochemical stability window, and this semi-solid electrolyte with a special structure can reduce the solvent demand and reduce the interface side reactions of the solid-state battery. DETAILED DESCRIPTION
[0046] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0047] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0048] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0049] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0050] In a first aspect, the present invention provides a method for preparing a semi-solid electrolyte, comprising the following steps:
[0051] (a) The activated MOF material is mixed with 2,4,3,5-di-O-methylene-D-gluconic acid and a solvent and subjected to a grafting reaction. After the grafting reaction is completed, solid-liquid separation is performed to obtain a MOF-glucose complex.
[0052] (b) mixing the MOF-glucose complex, a binder and a solvent to obtain a slurry, forming the slurry into a film, and then immersing the film in an electrolyte, and drying after the immersion is completed to obtain the semi-solid electrolyte.
[0053] This method can obtain a semi-solid electrolyte of MOF material of chemically grafted polyether molecules (2,4,3,5-di-O-methylene-D-gluconic acid), which has high room temperature ionic conductivity and uniform structure, good stability as a diaphragm, and the assembled battery has excellent cycle performance.
[0054] Specifically, semi-solid electrolytes mainly improve ion conductivity by adding ionic electrolytes. The present invention grafts polyether molecules (2,4,3,5-di-O-methylene-D-gluconic acid) into the activated MOF material. On the one hand, the polyether molecules themselves have ionic conductivity and can act as liquid electrolytes, reducing the amount of solvent used. On the other hand, the polyether molecules can solidify the electrolyte and reduce the loss of the electrolyte during the heat treatment process. At the same time, the semi-solid electrolyte prepared in situ is more uniform, and the lithium ion conductivity of the diaphragm obtained after immersion in the electrolyte is better. In addition, the activated MOF material is more conducive to the grafting of 2,4,3,5-di-O-methylene-D-gluconic acid.
[0055] The semi-solid electrolyte prepared by the above method has a higher lithium ion transfer coefficient and a wider electrochemical stability window, and this special structure of the semi-solid electrolyte can reduce the solvent demand and reduce the interface side reactions of the solid-state battery. Specifically, the MOF material itself has a stable chemical structure, a large specific surface area and uniformly distributed active sites, and the grafted polyether molecules can participate in ion transfer, improve ion conductivity, and reduce the amount of solvent used. And the stable crystal structure of MOF can have higher oxidation resistance at high voltage, so it shows a wider electrochemical stability window.
[0056] In some specific embodiments, in step (a), the 2,4,3,5-di-O-methylene-D-gluconic acid is mainly obtained by aldol condensation reaction of paraformaldehyde, D-gluconic acid-1,5-lactone and acid.
[0057] In some specific embodiments, in step (a), in order to improve the reaction rate, product yield and product quality of preparing 2,4,3,5-di-O-methylene-D-gluconic acid, the mass ratio of the polyformaldehyde to the D-glucono-1,5-lactone is 4:1 to 4; including but not limited to any point value of 4:1, 4:2, 4:3, 4:4 or a range value between any two of them.
[0058] In some specific embodiments, in step (a), the acid includes at least one of concentrated hydrochloric acid and concentrated sulfuric acid. Acidic conditions can reduce side reactions during the condensation reaction and improve the yield; at the same time, acidic conditions can promote further dehydration of the reactants, which is beneficial to the reaction; furthermore, the product generated under acidic conditions is more stereoscopic, which is more conducive to the formation of dendritic compounds and is beneficial to improving the ionic conductivity of the final product.
[0059] In some specific embodiments, in step (a), in order to further improve the reaction rate and quality of preparing 2,4,3,5-di-O-methylene-D-gluconic acid, the temperature of the aldol condensation reaction is 100-120°C; including but not limited to any one of 100°C, 105°C, 110°C, 115°C, 120°C or a range between any two of them.
[0060] In some specific embodiments, in step (a), in order to further improve the product yield and production efficiency of preparing 2,4,3,5-di-O-methylene-D-gluconic acid, the time of the aldol condensation reaction is 0.5 to 4 hours; including but not limited to any one of 0.5 hours, 1 hour, 2 hours, 3 hours, and 4 hours, or a range of values between any two of them.
[0061] In some specific embodiments, in step (a), the aldol condensation reaction is continuously stirred to promote the completion of the reaction.
[0062] In some specific embodiments, in step (a), the paraformaldehyde, the D-glucono-1,5-lactone and the acid are first mixed and subjected to an aldol condensation reaction, followed by solid-liquid separation, washing and drying to obtain the 2,4,3,5-di-O-methylene-D-gluconic acid. Specifically, the washing method includes water washing, for example, repeated washing with ultrapure water until the pH reaches neutral, and then drying in a vacuum drying oven at 90 to 120° C. for 24 to 48 hours.
[0063] In some specific embodiments, in step (a), in order to further improve the ionic conductivity and stability of the semi-solid electrolyte, the mass ratio of the activated MOF material and the 2,4,3,5-di-O-methylene-D-gluconic acid is 7 to 9:2 to 3; including but not limited to any point value of 7:2, 7:3, 8:2, 8:3, 9:2, 9:3 or a range value between any two of them.
[0064] In some specific embodiments, in step (a), in order to further improve the reaction rate and product yield of the grafting reaction, the temperature of the grafting reaction is 60-90°C; including but not limited to any one of 60°C, 70°C, 80°C, 90°C or a range between any two of them.
[0065] In some specific embodiments, in step (b), the grafting reaction time is 24 to 48 hours, including but not limited to any point value of 24 hours, 30 hours, 36 hours, 40 hours, 44 hours, 48 hours, or a range value between any two of them.
[0066] In some specific embodiments, in step (b), the grafting reaction is continuously stirred to promote a complete reaction.
[0067] In some specific embodiments, in step (b), the solvent includes water and / or an organic solvent, preferably water.
[0068] In some specific embodiments, in step (b), the solid-liquid separation further includes the steps of washing and drying.
[0069] In some specific embodiments, in step (a), the method for preparing the activated MOF material comprises: immersing the MOF material in an activating agent for activation.
[0070] In some specific embodiments, the activator includes at least one of acetone, acetonitrile, ethanol and dichloromethane. Soaking the MOF material with the activator can remove the ligand molecules and some solvent molecules that are not involved in the synthesis in the MOF skeleton pores, which is more conducive to the grafting of 2,4,3,5-di-O-methylene-D-gluconic acid.
[0071] In some specific embodiments, the MOF material includes at least one of MOF-808, UiO-66 and UiO-67.
[0072] In some specific embodiments, the activation time is 3 to 6 days.
[0073] In some specific embodiments, after the activation, the MOF material is vacuum dried at 100-130° C. for 36-72 hours, and then the grafting reaction is performed.
[0074] In some specific embodiments, the preparation method of MOF-808 includes: weighing zirconium oxychloride and 1,3,5-trimethylbenzene tricarboxylic acid in a mass ratio of 10:1-3 (including but not limited to any point value of 10:1, 10:2, 10:3 or any range value between the two), mixing with DMF (N,N-dimethylformamide) and formic acid, reacting at 140-160°C (including but not limited to any point value of 140°C, 145°C, 150°C, 155°C, 160°C or any range value between the two) for 24-48h (including but not limited to any point value of 24h, 28h, 32h, 36h, 40h, 48h or any range value between the two), then solid-liquid separation, washing and drying to obtain the MOF-808. Wherein, the volume ratio of DMF and formic acid can be 10:4-8.
[0075] In some specific embodiments, in step (b), the mass ratio of the MOF-glucose complex to the binder is 6-9:1-4; including but not limited to any point value of 6:1, 7:1, 8:1, 9:1, 6:2, 7:2, 8:2, 9:2, 6:3, 7:3, 8:3, 9:3, 6:4, 7:4, 8:4, 9:4 or the range value between any two of them.
[0076] In some specific embodiments, in step (b), the binder includes at least one of PTFE (polytetrafluoroethylene), PVDF (polyvinylidene fluoride) and CMC (sodium carboxymethyl cellulose).
[0077] In some specific embodiments, in step (b), the solvent includes water and / or an organic solvent, preferably an organic solvent, wherein the organic solvent includes at least one of ethanol, methanol and dichloromethane.
[0078] In some specific embodiments, in step (b), grinding is performed during the mixing process.
[0079] In some specific embodiments, in step (b), the method of making the slurry into the film comprises: coating the slurry on the surface of a substrate and then drying it, and then applying a pressure of 8 to 12 MPa and maintaining it for 20 to 40 minutes to obtain the film.
[0080] In some specific embodiments, in step (b), the lithium salt in the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluorosulfonyl)imide, and the organic solvent in the electrolyte includes at least one of ethylene carbonate, dimethyl carbonate and propylene carbonate.
[0081] As an example, the electrolyte may be a mixed solution of lithium hexafluorophosphate dissolved in ethylene carbonate and dimethyl carbonate, or a mixed solution of lithium bis(difluorosulfonyl)imide dissolved in ethylene carbonate and dimethyl carbonate, or a mixed solution of lithium bis(trifluorosulfonyl)imide dissolved in propylene carbonate, but is not limited thereto.
[0082] In some specific embodiments, in step (b), the molar concentration of the lithium salt in the electrolyte is 1 to 1.2 mol / L.
[0083] In some specific implementations, in step (b), the mass ratio of the film to the electrolyte is 10:2-5.
[0084] In some specific embodiments, in step (b), the soaking time is 48 to 72 hours, including but not limited to any one of 48 hours, 52 hours, 56 hours, 60 hours, 64 hours, 68 hours, and 72 hours, or a range between any two of them.
[0085] In some specific embodiments, in step (b), after the soaking is completed, the mixture is dried in a vacuum drying oven at 70 to 100° C. for 12 to 24 hours. Drying can remove the solvent in the electrolyte, improve the battery energy density, and retain the lithium salt to improve the ionic conductivity of the semi-solid electrolyte; at the same time, drying can remove moisture and volatile impurities on the surface of the semi-solid electrolyte, improving the battery stability.
[0086] In a second aspect, the present invention provides a semi-solid electrolyte prepared by the method for preparing the semi-solid electrolyte.
[0087] The semi-solid electrolyte has high room temperature ionic conductivity and a uniform structure, and the semi-solid electrolyte has good stability. The battery made with the semi-solid electrolyte has excellent cycle performance, high energy density, high lithium ion transfer coefficient and wide electrochemical stability window.
[0088] In some specific embodiments, the ionic conductivity of the semi-solid electrolyte at 25°C is ≥1×10 -4 S cm -1 ; including but not limited to 1×10 -4 S cm -1 , 1.1×10 -4 S cm -1 , 1.2×10 -4 S cm -1 , 1.3×10 -4 S cm -1 , 1.5×10 -4 S cm -1 , 1.8×10 -4 S cm -1 , 2×10-4 S cm -1 Any point value in or any range of values between them.
[0089] In some specific embodiments, the capacity retention rate of the battery containing the semi-solid electrolyte after 500 cycles at 1C is ≥95%, including but not limited to any point value of 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 99% or a range value between any two of them.
[0090] In some specific embodiments, the lithium ion transfer coefficient of the battery containing the semi-solid electrolyte is ≥ 0.6, including but not limited to any point value of 0.61, 0.62, 0.64, 0.65, 0.68, 0.7 or a range of values between any two of them.
[0091] In some specific embodiments, the electrochemical stability voltage of the battery containing the semi-solid electrolyte is ≥5.4V, including but not limited to any point value of 5.4V, 5.5V, 5.6V or a range of values between any two of them.
[0092] In a third aspect, the present invention provides a lithium metal battery, comprising a semi-solid electrolyte prepared by the method for preparing the semi-solid electrolyte.
[0093] The lithium metal battery has excellent cycle performance, high energy density, high lithium ion transfer coefficient, and a wide electrochemical stability window.
[0094] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0095] Example 1
[0096] The method for preparing the semi-solid electrolyte provided in this embodiment comprises the following steps:
[0097] (1) Preparation of 2,4,3,5-di-O-methylene-D-gluconic acid: 20 g of paraformaldehyde and 20 g of D-gluconic acid-1,5-lactone (i.e., a mass ratio of 4:4) were added to 30 mL of concentrated hydrochloric acid with a molar concentration of 12 mol / L, and the mixture was stirred at 120°C for 0.5 h. After the reaction, the solid and liquid were separated, and the collected powder was repeatedly washed with ultrapure water until the pH reached neutral, and then dried in a vacuum drying oven at 100°C for 24 h to obtain 2,4,3,5-di-O-methylene-D-gluconic acid.
[0098] (2) Preparation of MOF-808: 0.7 g ZrOCl 2 8H 2 O and 0.15 g 1,3,5-tricarboxylic acid (i.e., mass ratio = 10:2.1) were dissolved in a mixed solution of 20 mL DMF and formic acid (volume ratio of the two was 10:6), respectively, stirred evenly and added into a reactor, reacted at 150 °C for 24 h, and the solid-liquid separation was performed after the temperature of the reactor was lowered to room temperature. The obtained precipitate was repeatedly washed with DMF and methanol, and then vacuum dried at 50 °C to obtain MOF-808.
[0099] (3) Preparation of MOF-glucose complex: The MOF-808 synthesized in step (2) was immersed in a sufficient amount of acetone for activation for 3 days, during which the acetone was replaced several times. After the immersion, the activated MOF was vacuum dried at 120°C for 36 hours. Then, the activated MOF-808 and the 2,4,3,5-di-O-methylene-D-gluconic acid prepared in step (1) were added to 50 mL of deionized water in a mass ratio of 8:3, and stirred at 80°C for 24 hours. After the reaction was completed, the product was collected by suction filtration, and then repeatedly rinsed with deionized water, and vacuum dried at 100°C for 24 hours to obtain a MOF-glucose complex.
[0100] (4) Preparation of semi-solid electrolyte: The MOF-glucose complex obtained in step (3) and PTFE are mixed in a mass ratio of 9:1, and then ground and mixed. During the process, ethanol is added to make the two mix evenly to obtain a mixed slurry. The mixed slurry is evenly coated on a clean panel, then dried and rolled into a flexible film. A pressure of 10 MPa is applied to the film and maintained for 30 minutes to obtain a film with uniform MOF pores. The obtained film is then placed in an electrolyte (lithium hexafluorophosphate is dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, where the concentration of lithium hexafluorophosphate is 1 mol / L, abbreviated as 1M LiPF 6 / EC:DMC (1:1 vol%)) for 48 h to allow a sufficient amount of electrolyte to be adsorbed in the pores of MOF, and then the soaked film was dried in a vacuum drying oven at 80°C for 12 h to obtain the final semi-solid electrolyte.
[0101] Example 2
[0102] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in embodiment 1, except that step (1) is: 20 g of paraformaldehyde and 5 g of D-gluconic acid-1,5-lactone (i.e., a mass ratio of 4:1) are added to 30 mL of concentrated sulfuric acid with a molar concentration of 12 mol / L, and the mixture is stirred and reacted at 100° C. for 4 h. After the reaction is completed, the solid and liquid are separated, and the collected powder is repeatedly washed with ultrapure water until the pH reaches neutral, and then dried in a vacuum drying oven at 100° C. for 24 h to obtain 2,4,3,5-di-O-methylene-D-gluconic acid.
[0103] Example 3
[0104] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in embodiment 1, except that step (2) is: 0.7 g ZrOCl 2 8H 2 O and 0.21 g 1,3,5-benzenetricarboxylic acid (i.e., mass ratio = 10:3) were respectively dissolved in a mixed solution of 20 mL DMF and formic acid (volume ratio of the two was 10:8), stirred evenly and added into a reactor, reacted at 160 °C for 32 h, and the solid-liquid separation was performed after the temperature of the reactor was lowered to room temperature. The obtained precipitate was repeatedly rinsed with DMF and methanol, and then vacuum dried at 50 °C to obtain MOF-808.
[0105] Example 4
[0106] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in embodiment 1, except that step (3) is as follows: MOF-808 is immersed in a sufficient amount of acetonitrile for activation for 3 days, during which the acetonitrile is replaced several times, and after the immersion, the activated MOF is vacuum dried at 120°C for 36 hours. Then the activated MOF and 2,4,3,5-di-O-methylene-D-gluconic acid are added to 50 mL of deionized water in a mass ratio of 9:2, and stirred at 70°C for 30 hours. After the reaction is completed, the product is collected by suction filtration, and then repeatedly rinsed with deionized water, and vacuum dried at 100°C for 24 hours to obtain a MOF-glucose complex.
[0107] Example 5
[0108] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in Example 1, except that in step (4), PTFE is replaced by PVDF, and the mass ratio of MOF-glucose complex to PVDF is 7:3.
[0109] Example 6
[0110] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in Embodiment 1, except that in step (4), a pressure of 12 MPa is applied to the film and maintained for 20 minutes.
[0111] Example 7
[0112] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in Example 1, except that step (2) is not performed, and in step (3), MOF-808 is replaced by an equal mass of UiO-66.
[0113] Example 8
[0114] The preparation method of the semi-solid electrolyte provided in this embodiment is basically the same as that in Example 1, except that step (2) is not performed, and in step (3), MOF-808 is replaced by an equal mass of UiO-67.
[0115] Comparative Example 1
[0116] The preparation method of the semi-solid electrolyte provided in this comparative example is basically the same as that of Example 1, except that step (1) and step (3) are not performed, and the MOF-glucose complex in step (4) is replaced by an equal mass of MOF-808 obtained in step (2).
[0117] Comparative Example 2
[0118] The preparation method of the semi-solid electrolyte provided in this comparative example is basically the same as that in Example 1, except that in step (2), MOF-808 is not activated, and the unactivated MOF-808 and 2,4,3,5-di-O-methylene-D-gluconic acid are mixed and reacted.
[0119] Comparative Example 3
[0120] The preparation method of the semi-solid electrolyte provided in this comparative example is basically the same as that in Example 1, except that in step (3), the mass ratio of activated MOF-808 and 2,4,3,5-di-O-methylene-D-gluconic acid is replaced with 3:8.
[0121] The ionic conductivity of the semi-solid electrolytes prepared in various embodiments and comparative examples at 25° C. is shown in Table 1.
[0122] The semi-solid electrolytes prepared in each embodiment and each comparative example were cut into small discs with a diameter of 14 mm as semi-solid electrolyte separators, and lithium sheets were used as negative electrodes and NCM613 as positive electrodes to assemble into 2032 batteries. Electrochemical performance tests (including electrochemical stable voltage, lithium ion transfer coefficient and capacity retention rate test of 1C cycle 500 cycles) were performed, and the results are shown in Table 1. The electrochemical performance test of the control group was also tested, and the results are shown in Table 1. The control group was: lithium sheets were used as negative electrodes, NCM613 as positive electrodes, 1M LiPF 6 / EC:DMC (1:1 vol%) mixed solution was used as the electrolyte, and Celgard 2500 separator was used.
[0123] Table 1 Performance test results of semi-solid electrolyte and its assembled battery
[0124]
[0125] It can be seen from Table 1 that, compared with Comparative Examples 1 to 3 and the control group, the semi-solid electrolytes prepared in Examples 1 to 6 have higher room temperature ionic conductivity.
[0126] At the same time, the lithium ion transfer coefficient of the battery assembled with the semi-solid electrolyte prepared in Example 1 is significantly higher than that of Comparative Examples 1 to 3 and the control group.
[0127] Moreover, the batteries assembled with the semi-solid electrolytes prepared in each embodiment have a wider electrochemical stability window, which indicates that the semi-solid electrolytes prepared in each embodiment have good stability; at the same time, the cycle performance of the batteries assembled with the semi-solid electrolytes prepared in each embodiment is significantly better than that of Comparative Examples 1 to 3 and the control group.
[0128] Specifically, in the semi-solid electrolyte of Comparative Example 1, since 2,4,3,5-di-O-methylene-D-gluconic acid is not grafted and unactivated MOF-808 is used, the residual reaction solvent and unreacted ligands in the MOF pores will block the pores, and the lack of grafted polyether molecules will significantly reduce the ionic conductivity.
[0129] Since the semi-solid electrolyte of Comparative Example 2 uses unactivated MOF-808, the residual reaction solvent and unreacted ligands in the MOF pores affect the subsequent grafting and coordination of 2,4,3,5-di-O-methylene-D-gluconic acid, which indicates that the grafting degree of the polyether molecules will affect the ionic conductivity of the semi-solid electrolyte to a certain extent.
[0130] The semi-solid electrolyte of Comparative Example 3 has an inappropriate mass ratio of activated MOF-808 and 2,4,3,5-di-O-methylene-D-gluconic acid, which results in the inability of excess 2,4,3,5-di-O-methylene-D-gluconic acid to be grafted onto the active sites in the MOF pores. At the same time, it adheres to the surface of the semi-solid electrolyte, affecting the ion transfer efficiency and reducing the energy density.
[0131] The control group used liquid electrolyte, and the electrochemical stable voltage, lithium ion transfer coefficient and capacity retention rate all decreased significantly.
[0132] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a semi-solid electrolyte, characterized in that: The steps include: (a), mixing the activated MOF material with 2,4,3,5-di-O-methylene-D-gluconic acid and a solvent and performing a grafting reaction, and then performing solid-liquid separation to obtain a MOF-glucose complex; (b) mixing the MOF-glucose complex, a binder and a solvent to obtain a slurry, forming the slurry into a thin film, immersing the film in an electrolyte, and drying the film to obtain the semi-solid electrolyte.
2. The method for preparing a semi-solid electrolyte according to claim 1, characterized in that: In step (a), the 2,4,3,5-di-O-methylene-D-gluconic acid is mainly obtained by an aldol condensation reaction of paraformaldehyde, D-gluconic acid-1,5-lactone and acid, and the aldol condensation reaction satisfies at least one of the following conditions: (1) The mass ratio of the paraformaldehyde to the D-glucono-1,5-lactone is 4:1-4; (2) the acid comprises at least one of concentrated hydrochloric acid and concentrated sulfuric acid; (3) The temperature of the aldol condensation reaction is 100 to 120° C.; (4) The aldol condensation reaction time is 0.5 to 4 hours; (5) stirring continuously during the aldol condensation reaction; (6) Firstly, the polyformaldehyde, the D-gluconic acid-1,5-lactone and the acid are mixed and subjected to aldol condensation reaction, followed by solid-liquid separation, washing and drying to obtain the 2,4,3,5-di-O-methylene-D-gluconic acid.
3. The method for preparing a semi-solid electrolyte according to claim 1, characterized in that: In step (a), at least one of the following conditions is met: (1) The mass ratio of the activated MOF material to the 2,4,3,5-di-O-methylene-D-gluconic acid is 7-9:2-3; (2) The temperature of the grafting reaction is 60 to 90° C.; (3) The grafting reaction time is 24 to 48 hours; (4) continuously stirring during the grafting reaction; (5) The solvent includes water and / or an organic solvent; (6) After the solid-liquid separation, the method further includes the steps of washing and drying.
4. The method for preparing a semi-solid electrolyte according to claim 1, characterized in that: In step (a), the method for preparing the activated MOF material comprises: immersing the MOF material in an activating agent for activation; Preferably, the activating agent comprises at least one of acetone, acetonitrile, ethanol and dichloromethane; Preferably, the MOF material includes at least one of MOF-808, UiO-66 and UiO-67; More preferably, the preparation method of the MOF-808 comprises: weighing zirconium oxychloride and 1,3,5-tricarboxylic acid in a mass ratio of 10:1-3, mixing with DMF and formic acid, reacting at 140-160° C. for 24-48 hours, then separating the solid from the liquid, washing and drying to obtain the MOF-808.
5. The method for preparing a semi-solid electrolyte according to claim 1, characterized in that: In step (b), at least one of the following conditions is met: (1) The mass ratio of the MOF-glucose complex to the binder is 6-9:1-4; (2) The binder includes at least one of PTFE, PVDF and CMC; (3) The solvent includes water and / or an organic solvent; preferably, the organic solvent includes at least one of ethanol, methanol and dichloromethane; (4) grinding during the mixing process; (5) The method of making the slurry into the film comprises: applying the slurry on the surface of a substrate, drying it, and then applying a pressure of 8 to 12 MPa for 20 to 40 minutes to obtain the film; (6) the lithium salt in the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluorosulfonyl)imide, and / or the organic solvent in the electrolyte includes at least one of ethylene carbonate, dimethyl carbonate and propylene carbonate; (7) The soaking time is 48 to 72 hours.
6. A semi-solid electrolyte obtained by the method for preparing a semi-solid electrolyte according to any one of claims 1 to 5.
7. The semi-solid electrolyte according to claim 6, characterized in that: The ionic conductivity of the semi-solid electrolyte at 25°C is ≥1×10 -4 S cm -1 ; And / or, the capacity retention rate of the battery containing the semi-solid electrolyte after 500 cycles at 1C is ≥95%.
8. The semi-solid electrolyte according to claim 6, characterized in that: The lithium ion transfer coefficient of the battery containing the semi-solid electrolyte is ≥0.
6.
9. The semi-solid electrolyte according to claim 6, characterized in that: The electrochemical stability voltage of the battery containing the semi-solid electrolyte is ≥5.4V.
10. A lithium metal battery, characterized in that: The invention comprises a semi-solid electrolyte prepared by the method for preparing a semi-solid electrolyte according to any one of claims 1 to 5.
Citation Information
Patent Citations
Composite solid electrolyte based on MOF three-dimensional skeleton support, and preparation method thereof
CN113285118A
Metal organic framework-polymer composite solid electrolyte as well as preparation method and application thereof
CN113937363A
Solid electrolyte based on MOF-based ionic conductor and preparation method and application thereof
CN114709470A
Metal organic framework-based solid electrolyte as well as preparation method and application thereof
CN117895072A
Preparation method of composite solid-state electrolyte membrane, prepared composite solid-state electrolyte membrane and application of composite solid-state electrolyte membrane
CN118867360A